2019
DOI: 10.3390/sports7100221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Combinations of Concentric and Eccentric Resistance Training Programs on Traditional and Alternative Hamstrings-to-Quadriceps Ratios

Abstract: Resistance training is often recommended for combined increases in traditional and alternative hamstrings-to-quadriceps (H:Q) ratios in order to reduce knee strength imbalance and associated hamstrings and knee ligament injury risk. The aim of this study was to investigate the effect of different concentric and eccentric resistance training programs on traditional and alternative H:Q ratios. Forty male volunteers were assigned to one of 4 groups: concentric quadriceps and concentric hamstrings (CON/CON, n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…At the same time, mechanoreceptors will also undergo morphological changes, including irregular edges and flat structures. Scholars [ 5 ] have confirmed that the number of mechanoreceptors is positively correlated with the level of proprioception in the knee joint. Ruas et al [ 5 ] pointed out in the study of muscle response to external force that a certain amount of exudation will affect the sensory afferents of the knee joint, thereby inhibiting the neuromuscular response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, mechanoreceptors will also undergo morphological changes, including irregular edges and flat structures. Scholars [ 5 ] have confirmed that the number of mechanoreceptors is positively correlated with the level of proprioception in the knee joint. Ruas et al [ 5 ] pointed out in the study of muscle response to external force that a certain amount of exudation will affect the sensory afferents of the knee joint, thereby inhibiting the neuromuscular response.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars [ 5 ] have confirmed that the number of mechanoreceptors is positively correlated with the level of proprioception in the knee joint. Ruas et al [ 5 ] pointed out in the study of muscle response to external force that a certain amount of exudation will affect the sensory afferents of the knee joint, thereby inhibiting the neuromuscular response. In addition, trauma, osteoarthritis, and pain have also been confirmed as unfavorable factors of proprioception [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…To maximize running and jumping performance, a correspondingly high peak torque value of the knee joint extensors is required [ 69 ]. The positive relationship between the H/Q ratio and 30 m sprint time may suggest the important role of knee joint extensors in sprint performance.…”
Section: Discussionmentioning
confidence: 99%
“…Greater amounts of muscle activation seemed to be associated with phases of possibly superior quadriceps recruitment when compared to the hamstrings during a FW bout [38], suggesting quadriceps soreness was expected to be greater than the hamstrings; however, this was not the result. A variety of factors may have led to these conclusions including: biomechanical alterations in stress and force transference [3], differences within anterior-posterior propulsion and braking forces [3], or disparities in hamstringsto-quadriceps strength ratios [38,44]. However, none of these adverse factors were actively measured during this study protocol.…”
Section: Discussionmentioning
confidence: 99%